TEORI DAN KEMAMPUAN MATEMATIS DALAM PERMAINAN KARTU GAPLE: KAJIAN ETNOMATEMATIKA - Fiki Alghadari; Aloisius Loka Son (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
This study was created for the purpose to know that in gaple card game had used a mathematics knowledge and ability. Gaple card is a domino card which was usually played two pairs of player, sit in arranged circularly so the paired of player will be on the face. Each player will handle some card which was drawn randomly. The purpose player of the gaple game is to be a winner games by points collection which was accumulated from each games session where are collecting of points based on the rules of play that be known and agreed. This ethnomathematics study is the one of example that a tradition not only contained the community social aspect but also it would utilize the probability theory. Playing gaple card as a vehicle for training of counting ability to high order thinking actually. The integration of the probability theory and high order thinking ability have been utilized a pair player to directed and then created a game session for finished with resulting many of points where are the game's pattern was done through a setting systematically